Perceptions of Different Generations Regarding Managerial Competencies in Restaurants - Carina Kleynhans; Malome Prince Shai; Antoinette Roeloffze (Journal of Economics and Behavioral Studies, 2018)
Managerial competencies of restaurant managers play a major role in motivating employees to be productive and to provide excellent service which, in turn, will lead to customer satisfaction. Drawing upon generational differences in work ethics and values, the authors examine the importance of managerial competencies in three age cohorts. A quantitative research design was selected using a structured questionnaire consisting of five competency domains. Data were collected from 180 restaurant managers and employees in restaurants in the City of Tshwane. The results of the Fisher exact test indicated that the importance of managerial competencies differed significantly in the three age groups. Significant differences existed for three leadership domains, two management domains, one interpersonal and one intrapersonal domain. No significant differences were recorded for the perceptions of the different age groups regarding the importance of the technical domain.  For the younger generation, the ability to grant employees the opportunity to grow was regarded as highly important by all respondents. The ability to maintain discipline in the workforce was perceived as less important by the youngest age group when it was compared to the other age groups. The youngest employees felt that the ability to be innovative was not as important unlike the perception of the older age groups.  The findings of this study could lead restaurant managers to a better understanding of the different generational groups, how to motivate them thereby ensuring job satisfaction and service quality.